Oral zinc sulphate reduces the recurrence rate and provides significant therapeutic effects for viral warts: A systematic review and meta-analysis of randomized controlled trials - Chen-Chi Wang; Wei-Xiang Wang; Po-Yuan Wu (PLoS ONE, 2025)
Zinc plays a crucial role in maintaining immune balance in the human body. Zinc is believed to substantially affect cytokine synthesis and signaling; thus potentially combating viral infections, including Human Papillomavirus infection, through various mechanisms. Several randomized controlled trials (RCTs) have investigated whether oral zinc sulphate can improve viral warts; however, no comprehensive data is currently available. Therefore, we conducted a meta-analysis to evaluate the effectiveness of oral zinc sulphate for the treatment of viral warts. On July 1, 2024, we performed an extensive database search on PubMed, Embase, Web of Science, Cochrane CENTRAL, and ClinicalTrials.gov. Initially, 952 studies were identified, and after screening, 7 studies were included in the final analysis. Our findings showed that the total clearance rate of warts was significantly higher in the oral zinc sulphate group than in the control group (risk difference = 0.288; 95% CI = 0.087–0.489; p = 0.005). Subgroup analysis revealed that this therapeutic effect was more pronounced in individuals with low initial plasma zinc levels (risk difference = 0.767; 95% CI = 0.649–0.885; p < 0.001). Additionally, meta-regression showed that rise in zinc ion levels post-treatment were correlated with better treatment outcomes (coefficient = 0.0068; p < 0.001). Furthermore, for patients receiving traditional warts treatment, combining oral zinc sulphate significantly reduced the 6-month recurrence rate (log risk ratio = −1.043; 95% CI = −1.666 – −0.420; p = 0.001). The most common treatment-related side effects were nausea (risk difference = 0.562; 95% CI = 0.088–1.036; p = 0.020) and vomiting (risk difference = 0.205; 95% CI = 0.092–0.317; p < 0.001). Based on this evidence, oral zinc sulphate monotherapy offers notable benefits to those avoiding conventional treatments, and when combined with traditional therapies for viral warts, it can notably reduce recurrence rates over six months.